THE EFFECT OF BIOLOGICAL AND ANORGANIC FERTILIZER TOWARD PHOSPHATE SOLID BACTERIAL POPULATION, THE PLANTS GROWTH, AND PAKCOY USING NUTRIENT FILM - Katrina Putri Utami; Mieke Rochimi Setyawati (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2018)
Nutrient Film Technique (NFT) is a kind of hydroponic techniques which uses inorganic fertilizer nutrients. The use of inorganic fertilizers can be substituted with biological fertilizers so that they are more environmentally friendly. The research on the combination of biological fertilizers and inorganic fertilizers for pakcoy (Brassica rapa L.) plant. Randomized Block Design (RBD) consisting of four treatments was used in this research. They were 100%, 75%, and 50% inorganic fertilizer and 100% biological fertilizer in three periodical times. This research was carried out in September 2017 to January 2018. The parameters observed in this study included Phosphate Solvent Bacteria (PSB), plant growth and pakcoy plants. The result shows that the provision of inorganic fertilizers and biological fertilizers is able to increase the PSB population, plant height, and pakcoy plants. The combination of 50% inorganic fertilizer and biofertilizer produces the best PSB population, plant height and the best result on pakcoy.PENGARUH PUPUK HAYATI DAN ANORGANIK TERHADAP POPULASI BAKTERI PELARUT FOSFAT, TINGGI TANAMAN, DAN HASIL TANAMAN PAKCOY PADA NUTRIENT FILM TECHNIQUESalah satu teknik hidroponik adalah Nutrient Film Technique (NFT). Sistem hidroponik ini masih menggunakan nutrisi berupa pupuk anorganik. Pemakaian pupuk anorganik dapat disubtitusi dengan pemakaian pupuk hayati sehingga lebih ramah lingkungan. Penelitian kombinasi pupuk hayati dan pupuk anorganik untuk tanaman pakcoy (Brassica rapa L.) pada sistem NFT ini menggunakan Rancangan Acak Kelompok (RAK) yang terdiri atas empat perlakuan yaitu 100%, 75%, dan 50% pupuk anorganik ditambah 100% pupuk hayati diulang tiga kali. Penelitian dilaksanakan pada bulan September 2017 sampai Januari 2018. Parameter yang diamati pada penelitian ini antara lain populasi Bakteri Pelarut Fosfat, tinggi tanaman, dan hasil tanaman pakcoy. Pemberian pupuk anorganik dan pupuk hayati dapat meningkatkan populasi BPF, tinggi tanaman, dan hasil tanaman pakcoy. Kombinasi pupuk anorganik 50% dan pupuk hayati menghasilkan populasi BPF, tinggi tanaman, dan hasil tanaman yang terbaik pada tanaman pakcoy.